High-Speed and Energy-Efficient Carry Look-Ahead Adder - Balasubramanian, Padmanabhan; Mastorakis, Nikos E. (Journal of low power electronics and applications, 2022)
The carry look-ahead adder (CLA) is well known among the family of high-speed adders. However, a conventional CLA is not faster than other high-speed adders such as a conditional sum adder (CSA), a carry-select adder (CSLA), and the Kogge–Stone adder (KSA), which is the fastest parallel-prefix adder. Further, in terms of power-delay product (PDP) that characterizes the energy of digital circuits, the conventional CLA is not efficient compared to CSLA and KSA. In this context, this paper presents a high-speed and energy-efficient architecture for the CLA. Many adders ranging from ripple carry to parallel-prefix adders were implemented using a 32-28 nm CMOS standard digital cell library by considering a 32-bit addition. The adders were structurally described in Verilog and synthesized using Synopsys Design Compiler. From the results obtained, it is observed that the proposed CLA achieves a reduction in critical path delay by 55.3% and a reduction in PDP by 45% compared to the conventional CLA. Compared to the CSA, the proposed CLA achieves a reduction in critical path delay by 33.9%, a reduction in power by 26.1%, and a reduction in PDP by 51.1%. Compared to an optimized CSLA, the proposed CLA achieves a reduction in power by 35.4%, a reduction in area by 37.3%, and a reduction in PDP by 37.1% without sacrificing the speed. Although the KSA is faster, the proposed CLA achieves a reduction in power by 39.6%, a reduction in PDP by 6.5%, and a reduction in area by 55.6% in comparison.